Freedom of thought and its limits for Nassif Nassar - faten, sofiane; bensaid, mohamed (Journal of Social Sciences and Humanities, 2023)
This research paper raises the problem of freedom of thinking and its limitations for Nassif Nassar and starts from a postulate that freedom of thinking is part of freedom, which is a human right and necessity, where Nassar understands freedom of thinking as based on the discovery of tho ught for itself, and its rationalization of how it produces ideas and how it interacts with life, enhancing that interaction with freedom, responsibly, and freedom of thinking is worthless if it remains locked in thought, so it is associated with freedom of action and freedom of expression, and emphasizes the existence of concepts that contributed to the crystallization of freedom of thinking in modern times, on top of the concept of Cogito Cartesian and what he proposes about freedom, which has become the responsibility that every intellectual demands to carry, and the concept of lights that overthrew The idea of power and domination over the human mind, as well as the concept of criticism, which expanded the horizon of creativity and overthrew the illusion of absolute truth, and the concept of difference, which is the true justification for freedom of thought through the multiplicity of concepts and the multiplicity of ideas resulting from different lived experiences, and no doubt ideological thinking, political bullying and sectarian intolerance as obstacles limiting the effectiveness of the mind towards creativity will disappear if freedom is achieved within a legal and moral framework.